Ministry of Tourism Decree No. 549 of the Year 2013 Issued on 21/7/2013 = وزارة السياحة قرار رقم 549 لسنة 2013 صادر بتاريخ 21/7/2013 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.